Participation of First-Time Voters in the 2024 Elections in Cirebon City - Dewi, Elsa Rana; Sephia, Adinda; Zulkarnaen, Iskandar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the participation of first-time voters in the 2024 Elections in Cirebon City, where participation is considered suboptimal due to limited political understanding, apathy, and low trust in government institutions. Using a descriptive qualitative method with data collected through documentation, interviews, and direct observation, the research applies sociological, psychological, and rational choice theories by Dennis Kavanagh as its analytical framework. Findings show that first-time voter participation remains low, reflected in the still high number of invalid ballots, which indicates inadequate use of voting rights. The main factors influencing this condition include unequal socialization by the KPU, distrust toward political institutions, social media influence, and minimal political literacy. These results highlight the need for more targeted political education and effective outreach to improve youth participation in future elections.